2020
DOI: 10.1186/s13722-020-00196-5
|View full text |Cite
|
Sign up to set email alerts
|

Choosing internet-based treatment for problematic alcohol use—why, when and how? Users’ experiences of treatment online

Abstract: Background Internet-based treatment has emerged as a cost-effective option for reaching people who for different reasons are not reached by traditional treatment. Internet-based treatment for problematic alcohol use, specifically, has been found to show results on par with other forms of treatment. However, in-depth knowledge of users’ experiences is required to understand what works, and what needs further development. The aim of this study is to investigate the help-seeking motives among users of an internet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
12
0
5

Year Published

2021
2021
2023
2023

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 24 publications
(32 citation statements)
references
References 30 publications
1
12
0
5
Order By: Relevance
“…One of the leading obstacles to seeking treatment is reported to be stigma; for example, because patients feel ashamed to be associated with the clinic and worry about what others might think [ 9 , 11 , 51 , 52 ]. This points to the relevance of offering an anonymous version of internet-based alcohol treatment as it might reach a group of non–treatment seekers not otherwise reached, for example, owing to stigma, as also suggested elsewhere [ 53 ].…”
Section: Discussionsupporting
confidence: 58%
“…One of the leading obstacles to seeking treatment is reported to be stigma; for example, because patients feel ashamed to be associated with the clinic and worry about what others might think [ 9 , 11 , 51 , 52 ]. This points to the relevance of offering an anonymous version of internet-based alcohol treatment as it might reach a group of non–treatment seekers not otherwise reached, for example, owing to stigma, as also suggested elsewhere [ 53 ].…”
Section: Discussionsupporting
confidence: 58%
“…One important challenge for future studies is to improve follow-up rates and adherence to interventions without reducing the willingness to use the interventions. Increased demands on users to identify themselves or have contact with a professional might make people who wish to remain anonymous or feel ashamed or stigmatized more reluctant to seek support [ 81 ]. Treatment-seeking increases the rates of recovery from alcohol dependence [ 82 ], and internet-based interventions seem to be a possible way to reach individuals currently not seeking treatment [ 83 ]; however, it is still unclear whether internet-based interventions actually increase treatment-seeking.…”
Section: Discussionmentioning
confidence: 99%
“…McCrabb et al [ 6 ] showed that internet-based interventions for smoking cessation can reach the majority of socially disadvantaged populations. Ekström et al [ 7 ] showed that, while introducing a new perception of distance between the patient and the clinician, internet-based treatment can offer a better sense of confidentiality and that offering diverse content for users to choose from (such as cognitive behavioral therapy modules, therapist support, and discussion forum) is appreciated by patients and may contribute to the attractivity of internet-based treatment [ 8 ].…”
Section: Special Issue Themesmentioning
confidence: 99%